Working Methods of Old-Russian Architects - Stepanov, Mikhail V. (Actual Problems of Theory and History of Art, 2013)
Professional secrets of old-Russian architects interested the scholars for a long time. Numerous published hypotheses are based on the idea of a special method of proportioning derived from the national traditions. This article proposes a different look on the problem. Working method is proposed to reconstruct the work of old-Russian architects, using the treatises of Vitruvius and Alberti, and the working method is considered as the sum of three components: 1) the proportioning (aesthetic in objective reality), 2) the method of determining dimensions, 3) ratio analysis (subjective, aesthetic or aesthetic consciousness). Studies of temples built in 11th‒15th cc. show that during this period: 1) the architects used a method with different combination of relations between aisles and tiers; 2) that architects didn’t use scale and proportioned drawings, 3) that it is impossible using proportional method to reconstruct the lost parts of the temples, as each temple is unique.